Perceptions of funding higher education: a comparative study of Botswana, Lesotho and Swaziland - Simelane, Salebona Sicelo (2007)
Inadequate funding of higher education in sub-Saharan Africa is a perennial problem. The inadequacy of financial resources is undermining the efforts of universities to produce educated citizens to engage in productive careers. Public universities' reliance on their governments for funding when there are many competing needs for public resources calls for attention. This thesis is an exploration of perceptions of university academics and administrators and government officials of current and future strategies for funding higher education in the small Commonwealth countries: Botswana, Lesotho and Swaziland. A combination of human capital and social capital theories was used as a guide for the development of this study. It is a qualitative study whose data were collected through semi-structured interviews and document analysis between March and June 2005. The data were analysed using a thematic comparative method. The findings reveal that government funding, student tuition fees, residence and meal fees and bank interest are the main sources of funding for each of the universities. The governments allocate funds to the universities in simple block grants for manpower development and for providing access to higher education. This is in a range of 54 to 68% which is significantly different from trends in sub-Saharan Africa. Each institution centrally allocates funds to its faculties and departments in accordance with prepared budgets. Budget holders in the offices of Deans of Faculty and Heads of Department control the resource spending at their levels. The universities prepare annual audited financial statements as a means of being accountable to stakeholders. The study also found that there are some innovations that are either in place or due to be implemented as future funding strategies. In each case government funding will continue, with governments planning to introduce cost-sharing with parents/students. Each university has ventured into revenue diversification or income generating activities in order to meet the shortfall in government funding. Notably, the University of Botswana and the University of Swaziland have each established a foundation to fundraise with the private sector, international organisations and alumni. Thus, social capital is built onto the universities' fundraising activities. There are challenges facing the three universities. University strategic plans are not being implemented in all three universities. All three universities cannot increase student fees at will. Government requires all parastatal organisations to declare unused funds at the end of the year in Botswana. This has implications on funding for the following year. The establishment of a second university in Botswana poses some funding uncertainties at the University of Botswana. Similarly, future funding may be negatively affected at the University of Swaziland and the National University of Lesotho because the former sometimes approaches the Chancellor for extra funding, a thing that could sour relations between the Government of Swaziland and the University. The National University of Lesotho's delay in producing and submitting audited financial statements to Government is cause for concern in Lesotho.